Martandang; Kearifan Lokal Dalam Mengatur Pergaulan Remaja Suku Mandailing - Bakhrul Khair Amal; Riadi Syafutra Siregar (Universitas Andalas, 2023)
This research to describe activities of Martandang in the Mandailing tribe which has changed/lost, even though it is a custom in regulating how to get along with teenagers before marriage and local wisdom values. This research used qualitative with ethnographic approach. Techniques of collecting data were carried out by in-depth interviews, participatory observation and the oral history with 10 native speakers who had done martandang. The results show that martandang activity has changed due to technological developments and modernization, so that most of the Mandailing youth now no longer carry out this tradition. Martandang contains local wisdom values that try to regulate the way teenagers get along by recognizing each other's personalities without violating the rules or violating the norms that apply in Mandailing customs, a way to maintain the chastity of women in socializing until marriage and maintain politeness in behavior. The activities of this tradition used local expressions that can be interpreted as local wisdom values of welfare and peace. The conclusion of this study is that a revitalization model is needed that can transform the meaning and function, values and norms contained in the local wisdom of Martandang in the Mandailing generation.